2018
DOI: 10.1126/sciadv.aau5096
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of log-periodic oscillations in ultraquantum topological materials

Abstract: Discovery of log-periodic quantum oscillations may open a new chapter in the nearly 90-year history of quantum oscillations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
101
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(107 citation statements)
references
References 60 publications
(193 reference statements)
6
101
0
Order By: Relevance
“…Similar to the Efimov effect discussed above, the short range boundary condition breaks it down to the discrete scale invariance and results in an infinite number of quasi-bound states forming a geometric sequence [10,11]. The experiment by Wang et al [12] reported the observation of such discrete scale invariance in single-crystal three-dimensional Dirac semi-metal ZrTe 5 . The ZrTe 5 crystallizes in a layered orthorhombic structure with the space group Cmcm.…”
Section: Research Highlightmentioning
confidence: 75%
See 1 more Smart Citation
“…Similar to the Efimov effect discussed above, the short range boundary condition breaks it down to the discrete scale invariance and results in an infinite number of quasi-bound states forming a geometric sequence [10,11]. The experiment by Wang et al [12] reported the observation of such discrete scale invariance in single-crystal three-dimensional Dirac semi-metal ZrTe 5 . The ZrTe 5 crystallizes in a layered orthorhombic structure with the space group Cmcm.…”
Section: Research Highlightmentioning
confidence: 75%
“…Nevertheless, these studies have so far been limited to atomic and nuclear systems. The recently published experiment by Wang et al [12] brings the Efimov physics into condensed matter system by observing such a universal discrete scaling symmetry in the topological semi-metals. The topological semi-metal has received considerable attentions in the past decades.…”
mentioning
confidence: 99%
“…The clearest case is the recent discovery in the layered bulk material ZrTe 5 , where 5 cycles of oscillations have been observed by further increasing the magnetic field when the lowest Landau level is occupied. Amazingly, the oscillations show clear ln(B) behavior [9], as seen in Figure 1, taken from this reference. The periodicity is entirely new: the peaks in the resistance are periodic in ln(B), not B or 1/B.…”
mentioning
confidence: 68%
“…The recently discovered topological semimetal, a family of 3D topological materials including Dirac semimetal, Weyl semimetal and node-line semimetal [13][14][15][16][17][18][19][20][21][22], serves as a good system to test the behaviors of 3D pseudorelativistic electron gas under high magnetic field, as its members usually have low QL fields and weak impurity scatterings [23][24][25]. Different anomalies on both magnetoresistance and magnetic torque have been observed in the QL regime in topological semimetal ZrTe 5 , TaAs and NbAs [25][26][27][28]. Lately, annihilation of Weyl nodes above the QL field, a unique feature reflecting topological nontriviality, is also observed in Weyl semimetal TaP and TaAs [29,30].…”
Section: Introductionmentioning
confidence: 99%